Expression of BCL2L12, a new member of apoptosis-related genes, in breast tumors - Talieri, Maroulio; Diamandis, Eleftherios P.; Katsaros, Nikos; Gourgiotis, Dimitrios; Scorilas, Andreas (Thrombosis and Haemostasis, 2003)
Apoptosis, a normal physiological form of cell death, is critically involved in the regulation of cellular homeostasis. If the delicate balance between cell death and cell proliferation is altered by a defect in the normal regulation of apoptosis signaling, a cell population is able to survive and accumulate, thereby favoring the acquisition of further genetic alterations and promoting tumorigenesis. Dysregulation of programmed cell death mechanisms plays an important role in the pathogenesis and progression of breast cancer, as well as in the responses of tumors to therapeutic intervention. Overexpression of anti-apoptotic members of the Bcl-2 family such as Bcl-2 and Bcl-XL has been implicated in cancer chemoresistance, whereas high levels of pro-apoptotic proteins such as Bax promote apoptosis and sensitize tumor cells to various anticancer therapies. Recently, a new member of the Bcl-2 family, BCL2L12, was cloned. The BCL2L12 gene is constitutively expressed in many tissues, suggesting that the encoded protein serves an important function in different cell types. In the present study, the expression of BCL2L12 gene was analyzed by reverse transcription-PCR (PT-PCR) in 70 breast cancer tissues. Our results indicate that BCL2L12 positive breast tumors are mainly of lower stage (I/II) or grade (I/II) (p=0.02 or p=0.04 respectively). Cox regression analysis revealed that BCL2L12 expression is positively related to disease-free (DFS) and overall survival (OS) at both univariate and multivariate analysis (p=0.021, p=0.029, p=0.032, p=0.044 respectively). Kaplan-Meier survival curves also demonstrated that patients with BCL2L12-positive tumors have significantly longer DFS and OS (p=0.002 and p<0.001 respectively). BCL2L12 expression may be regarded as a new independent favorable prognostic marker for breast cancer.Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September, 2002.
Keywords: Apoptosis; BCL2L12; Bcl2 gene family; breast cancer; prognostic markers